Partisipasi Buruh Perempunan Dalam Berserikat Di Kabupaten Tangerang â Banten Studi Kasus : Perusahaan Sepatu dan Perusahaan Garment - , KURNIAWATI, Dr. Phil. Gabriel Lele, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The policy labor since new order has change the union system from single union system into a multi-union system. It is mean participation of labor in the union system has been open as wide as possible. But many workers are reluctant actively to organize in the union labor, especially women. The patterns of political participation will be related with participation of labor in the union labor, and will be divide into level of participation. There are, high of participation, low and did not participate at all. Qualitative research methods used in this study with in-depth interview techniques to labors in accordance with the level of participation of women labors. And then participation can be seen from participation in the membership and activities of trade unions. Two of the company's footwear and garment be case in this study. Both of companies are known level of participation and the impact of female labor participation in the association. There are two factors will become determinants of labor participation is the union labor and familyâs factors.